Estetika imaginatif dalam wacana Hadith Empat Puluh susunan al-Nawawi / Mohd Zuhdi Ismail - Mohd Zuhdi, Ismail (2018)
This study discusses the aesthetic values and imaginative elements of the discourse. The discourse focused is Forty Hadith by Imam Nawawi (r.h). Aesthetic values are defined as the element of balaghah included in the discourse. This values are analyzed based on the analysis of balaghah done according to the approach or guidelines as practised by Ibn al-Daynuriyy Qutaybat. The guidelines are al-haqiqat wa al-majaz, al-i‘jaz, suitability phrases with situation, al-taqdim wa al-ta’khir, al-ijaz, repeat dan rise sentence structure, uslub insya’, tasybih (simile), isti‘arat, kinayat wa ta‘rid. Imaginative on the other hand, are based on the approuch of literature criticism which focuses on the fundamental and literature methods as practised by Sayyid Qutb. There are al-harakat, al-hiwar, dilalat alfaz, psychology, al-khayal, dan tanasuq fanniyy These two approaches outline the concept of meaning, literally and figuratively of the discourse. Finally, an in-depth discourse analysis is done to measure and ensure the communicative level of a sentence and text produced as a discourse. The data collecting method used is library research, and the data collected is analyzed by using inductive approach and making comparison. Discourse analysis is used to analyze the language used within the specific social and cognitive context. The method discourse analysis is used to analyze the language in a social context and cognitive. It is found that the use of language based on the element of balaghah and literature has made the content of Hadith Nabawi applicable to the language discourse of the Prophet (Peace be Upon Him), and understandable to the companions (r.a) and the rest of the readers.